α5β1 Integrin Signaling Mediates Oxidized LDL-Induced Inflammation and Early Atherosclerosis - Yurdagul, Arif (2014)
OBJECTIVE: Endothelial cell activation drives early atherosclerotic plaque formation. Both fibronectin deposition and accumulation of oxidized LDL (oxLDL) occur early during atherogenesis and both are implicated in enhanced endothelial cell activation. However, interplay between these responses has not been established. The objective of our study was to determine whether endothelial matrix composition modulates the inflammatory properties of oxLDL. APPROACH AND RESULTS: We now show that oxLDL-induced NF-κB activation, proinflammatory gene expression, and monocyte binding is significantly enhanced when endothelial cells are attached to fibronectin compared to basement membrane proteins. This enhanced response does not result from altered oxLDL receptor expression, oxLDL uptake, or reactive oxygen species production, but instead results from oxLDL-induced activation of the fibronectin-binding integrin α5β1. Preventing α5β1 signaling (blocking antibodies, knockout cells) inhibits oxLDL-induced NF-κB activation and VCAM-1 expression. Furthermore, oxLDL-drives α5β1-dependent integrin signaling through the focal adhesion kinase (FAK) pathway and FAK inhibition (PF-573228, siRNA) blunts oxLDL-induced NF-κB activation, VCAM-1 expression, and monocyte adhesion. Lastly, treatment with the α5β1 signaling inhibitor, ATN-161, significantly blunts atherosclerotic plaque development in ApoE deficient mice, characterized by reduced VCAM-1 expression and macrophage accumulation without affecting fibrous cap size. CONCLUSIONS: Our data suggest that α5β1-mediated crosstalk between fibronectin and oxidized LDL regulates inflammation in early atherogenesis and therapeutics that inhibit α5 integrins may reduce inflammation without adversely affecting plaque structure.